Organizaciones de base territorial en la conservación de suelo del suroeste de Córdoba - Canale, Alejandra; Tamiozzo, Laura Virginia; Toledo, Marcelo; Zacchi, Eduardo (Facultad de Agronomía y Veterinaria, Universidad Nacional de Río Cuarto, 2024)
Poster